RANCANG BANGUN WEBSITE TRACER ALUMNI AKN PUTRA SANG FAJAR BLITAR - M Nur Fu'ad; Adimas Ketut Nalendra; Elok Hastari C (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
Tracer study is a method used to get feedback from alumni to tertiary institutions. Tracer alumni can be used to determine the absorption of PSN Blitar AKN alumni in the business world and industry. In addition, it also serves as a reference for adjusting competencies that must be owned by prospective alumni of AKN PSF Blitar in accordance with the needs of the business world and industry. System development uses the waterfall method which has several stages, including planning, analysis, design, implementation, and testing. The technology used in this system is web-based which aims to facilitate users in filling out the questionnaire and can be wider in scope. The result of this system design is a system design that uses a use case, the system flow uses a flowchart and the design of the physic data model. The results obtained are a web-based system that can reach a wider user, this system reduces operational costs, restrictions on access rights and individual alumni reports. Conclusion: This system can help universities in conducting tracer studies easily. The system used is web-based which can reach alumni wherever they are so that alumni do not need to come to campus or send questionnaire data so that the data will be faster to process.